Transformasi Pemanfaatan Lahan Gambut menjadi Destinasi Eduwisata Lebah Madu - Mashur, Dadang Mashur (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract Post-fire peatlands in Tanjung Leban Village, Bandar Laksamana District, Bengkalis Regency often leave environmental and socio-economic problems for the surrounding community. Through this community service program, efforts are being made to transform peatland utilization into a honeybee educational tourism destination as an alternative sustainable solution for ecosystem conservation, educating the public about the importance of peatland preservation, and strengthening the local economy through nature-based tourism activities. The goal is to empower local communities to manage peatlands productively, increase their capacity in honeybee cultivation, and develop the potential for environmentally-based educational tourism. Methods used include outreach, technical training in honeybee cultivation, strengthening community group institutions, and designing peat conservation-based educational tourism packages. The results of the activity indicate an increase in community knowledge and skills in beekeeping, an increase in alternative income sources through honey sales and tourism services, and a growing collective awareness of the importance of preserving peat ecosystems. Furthermore, multi-stakeholder support from the community, local government, companies, and academic partners strengthens the sustainability of the program. Thus, the transformation of peatland utilization into a honeybee educational tourism destination not only provides economic impacts, but also social and ecological ones, while supporting the green development agenda in peatland areas. Keywords: Peatland; Educational Tourism; Honey Bees; Empowerment; Sustainability Abstrak Lahan gambut pasca kebakaran di Desa Tanjung Leban Kecamatan Bandar Laksamana Kabupaten Bengkalis sering meninggalkan permasalahan lingkungan dan sosial-ekonomi bagi masyarakat sekitar. Melalui program pengabdian kepada masyarakat ini, dilakukan upaya transformasi pemanfaatan lahan gambut menjadi destinasi eduwisata lebah madu sebagai alternatif solusi berkelanjutan untuk konservasi ekosistem, edukasi masyarakat tentang pentingnya menjaga lahan gambut, serta memperkuat ekonomi lokal melalui kegiatan wisata berbasis alam. Tujuan untuk memberdayakan masyarakat lokal dalam mengelola lahan gambut secara produktif, meningkatkan kapasitas mereka dalam budidaya lebah madu, serta mengembangkan potensi wisata edukatif berbasis lingkungan. Metode yang digunakan meliputi sosialisasi, pelatihan teknis budidaya lebah madu, penguatan kelembagaan kelompok masyarakat, serta perancangan paket eduwisata berbasis konservasi gambut. Hasil kegiatan menunjukkan peningkatan pengetahuan dan keterampilan masyarakat dalam perlebahan, bertambahnya sumber pendapatan alternatif melalui penjualan madu dan jasa wisata, serta tumbuhnya kesadaran kolektif akan pentingnya menjaga ekosistem gambut. Selain itu, dukungan multi-pihak antara masyarakat, pemerintah daerah, perusahaan dan mitra akademik memperkuat keberlanjutan program. Dengan demikian, transformasi pemanfaatan lahan gambut menjadi destinasi eduwisata lebah madu tidak hanya memberikan dampak ekonomi, tetapi juga sosial dan ekologis, sekaligus mendukung agenda pembangunan hijau di wilayah gambut. Kata kunci: Lahan Gambut; Eduwisata; Lebah Madu; Pemberdayaan; Keberlanjutan